Effects of different rehabilitation provision systems on functional recovery in patients with subacute stroke. Issue 10 (14th September 2021) - Kimura, Yosuke; Suzuki, Mizue; Ichikawa, Takeo; Otobe, Yuhei; Koyama, Shingo; Tanaka, Shu; Hamanaka, Koji; Tanaka, Naoki; Yamada, Minoru
Abstract: Background: The extent of rehabilitation is a key element in promoting functional recovery in patients with stroke. However, the type of rehabilitation therapy that should be provided to improve functional outcomes remains unclear. Objective: To compare the effects of three different rehabilitation provision systems, namely conventional rehabilitation therapy, conventional rehabilitation therapy plus physical therapy (PT) on weekends, and conventional rehabilitation therapy plus PT and occupational therapy (OT) on weekends, on functional recovery in patients with subacute stroke. Design: Retrospective observational cohort study. Setting: Convalescence rehabilitation hospital. Patients: Three hundred one patients with subacute stroke (mean age, 69.7 ± 12.8 years). Interventions: Patients were classified into three groups according to rehabilitation therapy they received: a conventional group (only weekdays PT and OT; n = 70), an additional PT group (additional PT on weekends; n = 119), and an additional PT + OT group (additional PT and OT on weekends; n = 112). Main Outcome Measure: Functional Independence Measure (FIM) effectiveness was calculated as (discharge FIM ‐ admission FIM/maximum FIM − admission FIM) × 100. A multivariate general linear model was used to assess the difference in FIM effectiveness among the groups. Results: The mean FIM effectiveness in the conventional, additional PT, and additional PT + OT groups were 39.3 ± 30.1, 43.4 ± 33.2, and 54.3 ± 29.1, respectively. The multivariate analysis revealed a significant difference in FIM effectiveness among the three groups ( p = .036), and the η p 2 was 0.02, indicating a small effect. The additional PT + OT group showed significantly greater improvements in FIM effectiveness than the conventional group (mean difference = 8.78, SE = 3.58, 95% confidence interval: 0.17–17.39). Conclusions: This study showed that the additional PT + OT group had better functional recovery than did the conventional group. This indicates that increasing the amount of both PT and OT can promote poststroke functional recovery.